Uncovering Factors Influencing the Decision to Use Open Islamic Banking in East Java - khairul Ibad; Ahmad Tibrizi Soni Wicaksono (LP2M IAIN Palopo, 2026)
This study aims to identify factors influencing Generation Z’s decision to use Open Islamic Banking. A quantitative exploratory approach was applied using Exploratory Factor Analysis (EFA) on data collected from 388 purposively selected respondents in East Java, Indonesia. The instrument comprised 54 items representing key constructs such as perceived usefulness, perceived ease of use, attitude, behavioral intention, actual use, subjective norm, perceived behavioral control, and religiosity. The results reveal 13 factors explaining 55.062% of total variance, with perceived ease of use and perceived usefulness as dominant factors, while religiosity emerges as a distinctive determinant in the Islamic banking context. These findings indicate that technological, social, psychological, and religious aspects jointly influence usage decisions. The study implies that Islamic banking providers should enhance system usability, perceived benefits, and Sharia compliance to increase adoption among Generation Z. Future studies are suggested to apply confirmatory methods and broader samples. This article includes 54 items, 7 tables, 1 figure, and supporting references.